Anaerobic co-metabolic biodegradation of pharmaceuticals and personal care products driven by glycerol fermentation - Carneiro, Rodrigo B; Gomes, Gisele M; Camargo, Franciele P [UNESP]; Zaiat, Marcelo; Santos-Neto, Álvaro J (Elsevier, 2024)
Anaerobic digestion in two sequential phases, acidogenesis and methanogenesis, has been shown to be beneficial for enhancing the biomethane generation from wastewater. In this work, the application of glycerol (GOH) as a fermentation co-substrate during the wastewater treatment was evaluated on the biodegradation of different pharmaceuticals and personal care products (PPCPs). GOH co-digestion during acidogenesis led to a significant increase in the biodegradation of acetaminophen (from 78 to 89%), ciprofloxacin (from 25 to 46%), naproxen (from 73 to 86%), diclofenac (from 36 to 48%), ibuprofen (from 65 to 88%), metoprolol (from 45 to 59%), methylparaben (from 64 to 78%) and propylparaben (from 68 to 74%). The heterotrophic co-metabolism of PPCPs driven by glycerol was confirmed by the biodegradation kinetics, in which kbio (biodegradation kinetics constant) values increased from 0.18 to 2.11 to 0.27-3.60 L g-1-VSS d-1, for the operational phases without and with GOH, respectively. The assessment of metabolic pathways in each phase revealed that the prevalence of aromatic compounds degradation, metabolism of xenobiotics by cytochrome P450, and benzoate degradation routes during acidogenesis are key factors for the enzymatic mechanisms linked to the PPCPs co-metabolism. The phase separation of anaerobic digestion was effective in the PPCPs biodegradation, and the co-fermentation of glycerol provided an increase in the generation potential of biomethane in the system (energetic potential of 5.0 and 6.3 kJ g-1-CODremoved, without and with GOH, respectively). This study showed evidence that glycerol co-fermentation can exert a synergistic effect on the PPCPs removal during anaerobic digestion mediated by heterotrophic co-metabolism.